Annular Pancreas: A Rare Cause of Duodenal Obstruction in Adults - Patra, Devi Prasad (Springer India, 2010)
Annular pancreas is an uncommon congenital anomaly which usually presents itself in infants and newborn. Rarely it can present in late adult life with wide range of clinical severities thereby making its diagnosis difficult. Pre-operative diagnosis is often difficult. CT scan can illustrate the pancreatic tissue encircling the duodenum. ERCP and MRCP are useful in outlining the annular pancreatic duct. Surgery still remains necessary to confirm diagnosis and bypassing the obstructed segment.We report a case of 61 year female presenting with duodenal obstruction due to annular pancreas.